Hoax dalam Perspektif Hukum Indonesia - Tansah Rahmatullah (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2018)
The massive use of social media to share information that is not accompanied by adequate media literacy can be a serious threat to the Indonesian nation if the shared information is containing slander messages, fake news, hate speech, provocation, SARA sentiment. The hoax is a negative opinion contain slander and others, can lead to a riot, a clash, insecurity feeling, fear, ruined one’s reputation and material lost. The problems relate to Hoax in the perspective of Indonesian law about how is hoax regulated in Indonesian law and also its legal liability. This research uses normative legal research methods using a normative juridical approach. The normative juridical approach is conducted by examining and analyzing secondary data in the form of primary, secondary, and tertiary legal materials. Based on the research, it is found that in Indonesia there is differences regulation in legislation which become legal protection for handling hoax as indicated by the existing of the legislation that regulates a criminal act with different qualification and different legal threats. There is confusion as to which legal rule to use, whether the positive rule (Criminal Code) or a rule that specifically regulates the criminal acts committed in the cyberspace, in other words, sui generis. It is necessary to make efforts to find a comprehensive legal concept that can resolve the hoax.